(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2026)
Background: Monkeypox virus (MPXV) has re-emerged as a major public health concern due to its expanding global spread. However, limited therapeutic options hinder disease control. Molecular docking offers a valuable computational approach for identifying potential antiviral candidates. Methods: This study docked several antiviral drugs, including tecovirimat, tipranavir, remdesivir, fluocinolone, molnupiravir, famciclovir, acyclovir, cidofovir, and brincidofovir, against the monkeypox poxin protein (Protein Data Bank Identification (PDB ID): 8C9K). These drugs were selected based on reported anti-orthopoxvirus activity, clinical availability, and frequent prescription. Drug-likeness screening identified promising inhibitors. Molecular docking was performed using PyRx v0.9.8 with a 25 × 25 × 25 Å grid centered on the active site (x = 28.7, y = 56.9, z = 37.3). Tecovirimat served as the reference drug. Adverse drug monitoring event (ADME) and toxicity predictions assessed topological polar surface area, lipophilicity, solubility, bioavailability, blood–brain barrier permeability, P-glycoprotein interaction, median lethal dose (LD₅₀), and toxicity class by the Swiss ADME webtool. Results: Fluocinolone (−8.8 kcal/mol; Kilocalorie per mole), remdesivir (−8.9 kcal/mol), and tipranavir (−9.6 kcal/mol) showed stronger binding affinities than tecovirimat (−7.6 kcal/mol), while molnupiravir exhibited comparable affinity (−7.3 kcal/mol). The pharmacokinetic and toxicity profiles of fluocinolone, molnupiravir, and tipranavir were almost similar to the reference drug. Remdesivir showed minor physicochemical differences but was predicted to be safe. Conclusion: Tipranavir, remdesivir, fluocinolone, and molnupiravir emerged as promising MPXV poxin protein inhibitors, requiring further experimental validation.